PERANCANGAN WEBSITE INFOGRAFIS “CHANGE2O” SEBAGAI MEDIA EDUKASI PENGELOLAAN SAMPAH ORGANIK RUMAH TANGGA DENGAN METODE PENGOMPOSAN DI KOTA BANDUNG: Designing the "Change2O" Infographic Website as an Educational Media for Household Organic Waste Management Using Composting Method in Bandung City - Ananda Fadhilah; Intan Permata Sari (Jurnal Dimensi DKV: Seni Rupa dan Desain, 2024)
Designing the "Change2O" Infographic Website as an Educational Media for Household Organic Waste Management Using Composting Method in Bandung City. One of the goals of SDG Point 12 is closely related to the sustainable waste management process. Data shows that household organic waste ranks the highest in waste production in Indonesia. Following the Sarimukti landfill fire in Bandung, which was linked to the accumulation of organic waste, the government has implemented a policy prohibiting the disposal of organic waste at the Sarimukti landfill. The public is now expected to manage waste independently or in groups. This study aims to design an infographic website providing information and education on managing household organic waste. This digital educational tool is intended to be more practical, efficient, and engaging, using infographic displays to simplify the understanding of the information. The study employed the D&D method, conducted through six stages. Research participants included media and content expert validators, as well as housewife respondents aged 25-35 years in Bandung. The design of this infographic website received positive feedback and has been found to help improve understanding of organic waste management while also expanding new knowledge.